Evaluación del marketing digital y su influencia en el posicionamiento de marcas de cervezas artesanales en la provincia de Manabí - Cueva Solís, Jandry Javier (2025)
In the current context, digital marketing has become a key tool for brand strengthening, especially in highly competitive sectors such as craft beer production. The objective of this study was to evaluate digital marketing in order to determine its influence on the positioning of craft beer brands in the province of Manabí. The applied methodology followed a mixed approach with a descriptive, bibliographic, field, and exploratory design, allowing for a comprehensive understanding of the phenomenon related to digital marketing and brand positioning. The population consisted of craft breweries registered in the Ecuadorian Craft Brewers Association, selecting JagoBrewer and Beerkingo by convenience, along with a representative sample of their consumers. Analytical, correlational, inductive, and deductive methods were used for the analysis, as well as techniques such as surveys, the Likert scale, Pearson’s test, and Cronbach’s alpha coefficient. The main results revealed a strong visual and emotional brand recall, attributed to effective social media management, post-sale service, and engaging digital content. Furthermore, a positive correlation was observed between digital marketing strategies and brand positioning. In conclusion, digital marketing has proven to be a decisive factor in the positioning and growth of craft beer brands in Manabí.